High-temperature-resistant cable material and preparation method thereof

By adding a modified toughening agent and a composite stabilizer to the PVC cable material to form a material with a phosphate derivative and a silicone core layer structure, the defects of the existing PVC cable materials in terms of high temperature resistance, flame retardant and mechanical properties are solved, and higher material performance is achieved.

CN119684728APending Publication Date: 2025-03-25东莞庆龙电线电缆有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411985829.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing PVC cable materials have defects in high temperature resistance, flame retardant and mechanical properties, which are difficult to meet practical application needs.

Method used

PVC resin is used as the matrix and functional additives such as modified toughening agents and composite stabilizers are added. By modifying the phosphate derivatives and silicone core layer structure in the toughening agent, the material's high temperature resistance, flame retardant and mechanical properties are improved.

Benefits of technology

It significantly improves the high temperature resistance, flame retardant properties and mechanical properties of cable materials, ensuring higher stability and safety of the materials under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222550580000091
    Figure BDA0005222550580000091
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, and discloses a high-temperature-resistant cable material and a preparation method thereof. The cable material is prepared from the following raw materials in parts by weight: 100 parts of PVC (Polyvinyl Chloride) resin, 10 to 15 parts of maleic anhydride grafted ethylene propylene diene monomer, 8 to 12 parts of modified flexibilizer, 2.5 to 3.5 parts of compound stabilizer, 2 to 5 parts of nano silicon dioxide, 20 to 30 parts of plasticizer, 0.2 to 0.4 part of lubricant and 1 to 2 parts of antioxidant, according to the invention, PVC resin is used as a matrix, and functional aids such as a modified flexibilizer and a composite stabilizer are added, so that the high temperature resistance, flame retardance and mechanical properties of the matrix are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable materials, and in particular to a high temperature resistant cable material and a preparation method thereof. Background Art

[0002] PVC has the advantages of low cost, heat resistance, durability, environmental protection and easy recycling, so it is widely used as a coating material for electronic wires and cables. PVC wire material is often used to coat cables to form PVC wire sheath. The PVC wire sheath of the cable is an important protective layer to protect the wires inside the cable, and plays a role in moisture-proof, anti-corrosion, anti-aging, insulation, etc. It can also prevent the wires from being exposed and damaged, thereby improving the safety and service life of the cable. However, the cable materials synthesized with PVC resin as the main raw material still have certain defects in high temperature resistance, flame retardancy and mechanical properties, which are difficult to meet the needs.

[0003] Heat stabilizers are generally added to PVC cable materials to improve the thermal stability of the material and thus improve its high temperature resistance. Commonly used heat stabilizers are calcium zinc heat stabilizers, which are widely used in the PVC industry due to their high thermal stability, environmental protection and no heavy metals. However, the zinc chloride generated by these heat stabilizers during the stabilization process will cause PVC "zinc burn", which greatly weakens the stabilization effect of the calcium zinc heat stabilizer, thereby limiting the high temperature resistance of the cable material. Therefore, researchers need to develop a PVC cable material with excellent high temperature resistance, flame retardancy and mechanical properties to meet practical application needs. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high temperature resistant cable material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high temperature resistant cable material comprises the following raw materials in parts by weight: 100 parts of PVC resin, 10-15 parts of maleic anhydride grafted EPDM rubber, 8-12 parts of modified toughening agent, 2.5-3.5 parts of composite stabilizer, 2-5 parts of nano silicon dioxide, 20-30 parts of plasticizer, 0.2-0.4 parts of lubricant, and 1-2 parts of antioxidant;

[0007] Furthermore, the plasticizer is trioctyl trimellitate, the lubricant is polyethylene wax, and the antioxidant is antioxidant 1010;

[0008] Further, the composite stabilizer is a mixture of zinc stearate and an organic stabilizer, wherein the mass ratio of zinc stearate to the organic stabilizer is 1-3:1-3;

[0009] The modified toughening agent is prepared by the following steps:

[0010] Step A1, dispersing ethylenediaminetetramethylenephosphonic acid evenly in 1,4-dioxane, and heating to 45-55° C., slowly adding hydroxyethyl acrylate under nitrogen, reflux stirring and reacting for 6-10 hours, rotary evaporating and drying to obtain a phosphate derivative;

[0011] Further, in step A1, the usage ratio of ethylenediaminetetramethylenephosphonic acid, 1,4-dioxane and hydroxyethyl acrylate is 0.01 mol:50 mL:0.02-0.04 mol;

[0012] Step A2, after mixing deionized water, dodecylbenzene sulfonic acid and emulsifier (OP-10), heating to 40-50° C. and stirring for 30 min, slowly adding a mixture of ethyl orthosilicate and KH-570 (silane coupling agent), stirring and reacting for 1.5-2.5 h, cooling to room temperature, adjusting the pH to 8-9, and heating to 75-85° C., adding potassium persulfate, and then adding the acrylate mixture dropwise (adding within 2 h), and then adding an equal amount of potassium persulfate to react for 2-3 h, demulsifying, filtering, washing, and drying to obtain a modified toughening agent;

[0013] Further, in step A2, the usage ratio of deionized water, dodecylbenzenesulfonic acid, emulsifier, tetraethyl orthosilicate, KH-570, acrylate mixture and potassium persulfate is 30-40 mL: 0.35-0.4 g: 0.05-0.1 g: 23-24 g: 1-2 g: 79.25-87.25 g: 0.6 g;

[0014] Furthermore, in step A2, the acrylic acid mixture is prepared by mixing and stirring acrylic acid, butyl acrylate, methyl methacrylate, a phosphate derivative, sodium dodecyl sulfate and deionized water in a mass ratio of 1-3:10-15:3-4:10-15:0.25:50.

[0015] The organic stabilizer is prepared by the following steps:

[0016] Step B1, dispersing 1-(3-aminopropyl)imidazole and sodium hydroxide in acetonitrile, recorded as solution 1; dispersing cyanuric chloride and acetonitrile evenly in an ice water bath, slowly adding solution 1 dropwise, and reacting at 0-5° C. for 2-4 hours to obtain an intermediate product;

[0017] Further, in step B1, the dosage ratio of cyanuric chloride, acetonitrile and solution 1 is 0.01-0.03 mol: 100 mL: 50 mL;

[0018] Further, the dosage ratio of 1-(3-aminopropyl)imidazole, sodium hydroxide and acetonitrile in solution 1 of step B1 is 0.01-0.03 mol: 0.04-0.12 g: 50 mL;

[0019] Step B2, 5-aminoisophthalic acid and sodium hydroxide are dispersed in acetonitrile, recorded as solution 2; the intermediate product is heated to room temperature, and 1 / 2 of solution 2 is slowly added dropwise, the temperature is raised to 45-55°C for reaction for 4-6h, and then the temperature is raised to 90°C, and the remaining solution 2 is slowly added dropwise, and the temperature is maintained at reflux for reaction for 5-7h, and the pH of the system is adjusted to 6.5-7, and the solvent is distilled off to obtain an organic stabilizer;

[0020] Furthermore, the dosage ratio of 5-aminoisophthalic acid, sodium hydroxide and acetonitrile in solution 2 of step B2 is 0.02-0.06 mol: 0.08-0.24 g: 100 mL.

[0021] A method for preparing a high temperature resistant cable material comprises the following steps:

[0022] Step S1, weighing raw materials by weight: mixing PVC resin, modified toughening agent, composite stabilizer, nano-silicon dioxide, lubricant and antioxidant at 100-120° C. for 5-10 minutes, then heating to 150-170° C., adding plasticizer and maleic anhydride grafted EPDM rubber and continuing to stir for 4-7 minutes to obtain a mixture;

[0023] Step S2, placing the mixed material in a twin-screw extruder for extrusion and granulation to obtain a high temperature resistant cable material;

[0024] Furthermore, in step S2, the screw speed of the twin-screw extruder is 400-600 rpm / min, and the die discharge temperature is 175-185°C.

[0025] Beneficial effects of the present invention:

[0026] The cable material of the present invention is based on PVC resin, and functional additives such as modified toughening agents and composite stabilizers are added to improve the high temperature resistance, flame retardancy and mechanical properties of the base.

[0027] In the modified toughening agent, ethylenediaminetetramethylenephosphonic acid and hydroxyethyl acrylate are first reacted to obtain a phosphate derivative containing a multi-double bond structure; then tetraethyl orthosilicate and KH-570 are used as raw materials to obtain an organosilicon core layer, and then acrylic acid, butyl acrylate, methyl methacrylate and phosphate derivatives are used as raw materials to synthesize a polyacrylate shell layer to obtain a modified toughening agent. The introduction of the modified toughening agent improves the mechanical properties and flame retardant properties of the PVC matrix. This is because the active groups in the modified toughening agent can react chemically with the PVC resin to form a cross-linked structure. At the same time, when the PVC material is impacted, the modified toughening agent will deform. This deformation induces shear yielding of the PVC collective matrix, and can absorb impact energy during the deformation process to prevent the matrix material from being destroyed, thereby playing a toughening role. In addition, the phosphate structure and organosilicon structure introduced into the matrix also have flame retardant properties, which can effectively improve the flame retardant properties of the matrix and reduce the occurrence of fires.

[0028] Organic stabilizers are prepared by using cyanuric chloride as an intermediate and grafting 1-(3-aminopropyl)imidazole and 5-aminoisophthalic acid onto the intermediate. Composite stabilizers are compounded with organic stabilizers and zinc stearate, which can significantly improve the thermal stability of the PVC matrix and thus improve the high temperature resistance of the matrix; the carboxyl group in the organic stabilizer has a complexing effect on the ZnCl2 generated by zinc stearate, which can reduce the chloride concentration of zinc in the system and inhibit the catalytic effect of zinc chloride as a strong Lewis acid on the degradation of PVC, thereby reducing the thermal degradation of the PVC matrix at high temperatures and improving the high temperature resistance of the matrix; in addition, the organic stabilizer also contains triazine structures and imidazole structures with good thermal stability, which can further improve the thermal stability of the PVC matrix. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1: The modified toughening agent is prepared by the following steps:

[0031] Step A1, evenly disperse 0.01 mol of ethylenediaminetetramethylenephosphonic acid in 50 mL of 1,4-dioxane, and heat to 45°C. Slowly add 0.02 mol of hydroxyethyl acrylate under nitrogen, reflux and stir to react for 6 hours, rotary evaporate and dry to obtain a phosphate derivative;

[0032] Step A2, after mixing 30mL of deionized water, 0.35g of dodecylbenzenesulfonic acid and 0.05g of emulsifier (OP-10), heating to 40°C and stirring for 30min, slowly adding a mixture of 24g of ethyl orthosilicate and 1g of KH-570, stirring and reacting for 1.5h, cooling to room temperature, adjusting the pH to 8, and heating to 75°C, adding 0.3g of potassium persulfate, and then dropwise adding 79.25g of an acrylate mixture (the addition is completed within 2h), and then adding 0.3g of potassium persulfate to react for 2h, demulsifying, filtering, washing, and drying to obtain a modified toughening agent. The acrylate mixture is prepared by mixing and stirring acrylic acid, butyl acrylate, methyl methacrylate, phosphate derivatives, sodium dodecyl sulfate and deionized water in a mass ratio of 1g:15g:3g:10g:0.25g:50g.

[0033] The organic stabilizer is prepared by the following steps:

[0034] Step B1, 0.01 mol 1-(3-aminopropyl)imidazole and 0.04 sodium hydroxide were dispersed in 50 mL acetonitrile, recorded as solution 1; 0.01 mol cyanuric chloride and 100 mL acetonitrile were dispersed evenly in an ice water bath, 50 mL solution 1 was slowly added dropwise, and the mixture was reacted at 0° C. for 2 h to obtain an intermediate product;

[0035] Step B2, 0.02 mol 5-aminoisophthalic acid and 0.08 g sodium hydroxide were dispersed in 100 mL acetonitrile, recorded as solution 2; the intermediate product was heated to room temperature, and then 50 mL of solution 2 was slowly added dropwise, the temperature was raised to 45 ° C. and reacted for 4 hours, and then the temperature was raised to 90 ° C., and the remaining 50 mL of solution 2 was slowly added dropwise, and the temperature was maintained at reflux for 5 hours, and the pH of the system was adjusted to 6.5, and the solvent was distilled off to obtain an organic stabilizer.

[0036] The composite stabilizer is a mixture of zinc stearate and an organic stabilizer, wherein the mass ratio of zinc stearate to the organic stabilizer is 3g:1g.

[0037] Example 2: The modified toughening agent is prepared by the following steps:

[0038] Step A1, evenly disperse 0.01 mol of ethylenediaminetetramethylenephosphonic acid in 50 mL of 1,4-dioxane, and heat to 50° C., slowly add 0.03 mol of hydroxyethyl acrylate under nitrogen, reflux and stir to react for 8 h, rotary evaporate, and dry to obtain a phosphate derivative;

[0039] Step A2, 35mL deionized water, 0.37g dodecylbenzenesulfonic acid and 0.075g emulsifier (OP-10) were mixed, heated to 45 ° C and stirred for 30min, and then 23.5g of ethyl orthosilicate and 1.5g of KH-570 were slowly added, stirred and reacted for 2h, cooled to room temperature, adjusted to pH 8.5, and heated to 80 ° C, 0.3g of potassium persulfate was added, and then 80.25g of acrylate mixture was added dropwise (the addition was completed within 2h), and then 0.3g of potassium persulfate was added to react for 2.5h, demulsified, filtered, washed and dried to obtain a modified toughening agent. The acrylate mixture is prepared by mixing and stirring acrylic acid, butyl acrylate, methyl methacrylate, phosphate derivatives, sodium dodecyl sulfate and deionized water in a mass ratio of 2:12:3.5:12.5:0.25:50.

[0040] The organic stabilizer is prepared by the following steps:

[0041] Step B1, 0.02 mol 1-(3-aminopropyl)imidazole and 0.08 g sodium hydroxide were dispersed in 50 mL acetonitrile, recorded as solution 1; 0.02 mol cyanuric chloride and 100 mL acetonitrile were dispersed evenly in an ice water bath, 50 mL solution 1 was slowly added dropwise, and the mixture was reacted at 2° C. for 3 h to obtain an intermediate product;

[0042] Step B2, 0.04 mol 5-aminoisophthalic acid and 0.16 g sodium hydroxide were dispersed in 100 mL acetonitrile, recorded as solution 2; the intermediate product was heated to room temperature, and then 50 mL of solution 2 was slowly added dropwise, the temperature was raised to 50 ° C. and reacted for 5 h, and then the temperature was raised to 90 ° C., and the remaining 50 mL of solution 2 was slowly added dropwise, and the temperature was maintained at reflux for 6 h, and the pH of the system was adjusted to 6.7, and the solvent was distilled off to obtain an organic stabilizer.

[0043] The composite stabilizer is a mixture of zinc stearate and an organic stabilizer, wherein the mass ratio of zinc stearate to the organic stabilizer is 2:2.

[0044] Example 3: The modified toughening agent is prepared by the following steps:

[0045] Step A1, 0.01 mol of ethylenediaminetetramethylenephosphonic acid was evenly dispersed in 50 mL of 1,4-dioxane, and the temperature was raised to 55° C., and 0.04 mol of hydroxyethyl acrylate was slowly added under nitrogen, and the mixture was refluxed and stirred for 10 h, and then rotary evaporated and dried to obtain a phosphate derivative;

[0046] Step A2, after mixing 40mL of deionized water, 0.4g of dodecylbenzenesulfonic acid and 0.1g of emulsifier (OP-10), heating to 50°C and stirring for 30min, slowly adding a mixture of 23g of ethyl orthosilicate and 2g of KH-570, stirring and reacting for 2.5h, cooling to room temperature, adjusting the pH to 9, and heating to 85°C, adding 0.3g of potassium persulfate, and then dropwise adding 87.25g of acrylate mixture (addition is completed within 2h), and then adding 0.3g of potassium persulfate to react for 3h, demulsifying, filtering, washing, and drying to obtain a modified toughening agent. The acrylate mixture is prepared by mixing and stirring acrylic acid, butyl acrylate, methyl methacrylate, phosphate derivatives, sodium dodecyl sulfate and deionized water in a mass ratio of 3:15:4:15:0.25:50.

[0047] The organic stabilizer is prepared by the following steps:

[0048] Step B1, 0.03 mol 1-(3-aminopropyl)imidazole and 0.12 g sodium hydroxide were dispersed in 50 mL acetonitrile, recorded as solution 1; 0.03 mol cyanuric chloride and 100 mL acetonitrile were dispersed evenly in an ice water bath, 50 mL solution 1 was slowly added dropwise, and the mixture was reacted at 5° C. for 4 h to obtain an intermediate product;

[0049] Step B2, 0.06 mol 5-aminoisophthalic acid and 0.24 g sodium hydroxide were dispersed in 100 mL acetonitrile, recorded as solution 2; the intermediate product was heated to room temperature, and then 50 mL of solution 2 was slowly added dropwise, the temperature was raised to 55 ° C. and reacted for 6 hours, and then the temperature was raised to 90 ° C., and the remaining 50 mL of solution 2 was slowly added dropwise, and the temperature was maintained at reflux for 7 hours, and the pH of the system was adjusted to 7, and the solvent was distilled off to obtain an organic stabilizer.

[0050] The composite stabilizer is a mixture of zinc stearate and an organic stabilizer, wherein the mass ratio of zinc stearate to the organic stabilizer is 1:3.

[0051] Embodiment 4: A method for preparing a high temperature resistant cable material comprises the following steps:

[0052] 100 parts of PVC resin, 10 parts of maleic anhydride grafted EPDM rubber, 8 parts of the modified toughening agent prepared in Example 1, 2.5 parts of the composite stabilizer prepared in Example 1, 2 parts of nano-silicon dioxide, 20 parts of trioctyl trimellitate, 0.2 parts of polyethylene wax, and 10101 parts of antioxidant;

[0053] Step S1, weighing raw materials by weight: PVC resin, modified toughening agent prepared in Example 1, composite stabilizer prepared in Example 1, nano-silica, polyethylene wax and antioxidant 1010 are mixed and stirred at 100° C. for 5 minutes, then the temperature is raised to 150° C., trioctyl trimellitate and maleic anhydride grafted ethylene propylene rubber are added and stirred for 4 minutes to obtain a mixture;

[0054] Step S2: placing the mixed material in a twin-screw extruder for extrusion and granulation to obtain a high-temperature resistant cable material. The screw speed of the twin-screw extruder is 400 rpm / min, and the die discharge temperature is 175°C.

[0055] Embodiment 5: A method for preparing a high temperature resistant cable material comprises the following steps:

[0056] 100 parts of PVC resin, 12 parts of maleic anhydride grafted EPDM rubber, 10 parts of the modified toughening agent prepared in Example 2, 3 parts of the composite stabilizer prepared in Example 2, 3.5 parts of nano-silicon dioxide, 25 parts of trioctyl trimellitate, 0.3 parts of polyethylene wax, and 1.5 parts of antioxidant 1010;

[0057] Step S1, weighing raw materials by weight: PVC resin, modified toughening agent prepared in Example 2, composite stabilizer prepared in Example 2, nano-silica, polyethylene wax and antioxidant 1010 are mixed and stirred at 110° C. for 7 minutes, then the temperature is raised to 160° C., trioctyl trimellitate and maleic anhydride grafted ethylene propylene rubber are added, and stirring is continued for 5 minutes to obtain a mixture;

[0058] Step S2: placing the mixed material in a twin-screw extruder for extrusion and granulation to obtain a high-temperature resistant cable material. The screw speed of the twin-screw extruder is 500 rpm / min, and the die discharge temperature is 180°C.

[0059] Embodiment 6: A method for preparing a high temperature resistant cable material comprises the following steps:

[0060] 100 parts of PVC resin, 15 parts of maleic anhydride grafted EPDM rubber, 12 parts of the modified toughening agent prepared in Example 3, 3.5 parts of the composite stabilizer prepared in Example 3, 5 parts of nano-silicon dioxide, 30 parts of trioctyl trimellitate, 0.4 parts of polyethylene wax, and 10102 parts of antioxidant;

[0061] Step S1, weighing raw materials by weight: PVC resin, modified toughening agent prepared in Example 3, composite stabilizer prepared in Example 3, nano silicon dioxide, polyethylene wax and antioxidant 1010 are mixed and stirred at 120° C. for 10 min, then the temperature is raised to 170° C., trioctyl trimellitate and maleic anhydride grafted ethylene propylene rubber are added, and stirring is continued for 7 min to obtain a mixture;

[0062] Step S2, placing the mixed material in a twin-screw extruder for extrusion and granulation to obtain a high-temperature resistant cable material, the screw speed of the twin-screw extruder is 600 rpm / min, and the die discharge temperature is 185°C.

[0063] Comparative Example 1: This comparative example is a cable material. The difference from Example 6 is that zinc stearate is used instead of the composite stabilizer prepared in Example 3, and the rest is the same.

[0064] Comparative Example 2: This comparative example is a cable material. The difference from Example 6 is that the organic stabilizer prepared in Example 3 is used instead of the composite stabilizer prepared in Example 3, and the rest is the same.

[0065] Comparative Example 2: This comparative example is a cable material. The difference from Example 6 is that a commercially available PVC toughening agent is used instead of the modified toughening agent prepared in Example 3, and the rest are the same.

[0066] The cable materials prepared in Examples 4-6 and Comparative Examples 1-3 were subjected to performance tests:

[0067] Mechanical properties test: refer to the method of GB / T 1040.1-2006 to test tensile strength and elongation at break;

[0068] Flame retardant performance test: The limiting oxygen index is determined according to the method of GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method";

[0069] High temperature resistance test: According to the TG test, the sample was placed under nitrogen conditions, heated to 650°C at a rate of 10°C / min, and the stabilization time at 200°C was recorded;

[0070] The test results are shown in Table 1:

[0071] Table 1: Performance test results

[0072]

[0073] As can be seen from Table 1, the cable material prepared by the present invention has a tensile strength in the range of (19.3-22.1) MPa, an elongation at break in the range of (361-388)%, a limiting oxygen index in the range of (33-36)%, and a stability time at 200°C in the range of (85-90) min after being tested for mechanical properties, flame retardant properties and high temperature resistance, indicating that the cable material has excellent mechanical properties, flame retardant properties and high temperature resistance.

[0074] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high temperature resistant cable material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of PVC resin, 10-15 parts of maleic anhydride grafted EPDM rubber, 8-12 parts of modified toughening agent, 2.5-3.5 parts of composite stabilizer, 2-5 parts of nano silicon dioxide, 20-30 parts of plasticizer, 0.2-0.4 parts of lubricant and 1-2 parts of antioxidant; The modified toughening agent is prepared by the following steps: Step A1, dispersing ethylenediaminetetramethylenephosphonic acid evenly in 1,4-dioxane, and heating to 45-55° C., slowly adding hydroxyethyl acrylate under nitrogen, reflux stirring and reacting for 6-10 hours, rotary evaporating and drying to obtain a phosphate derivative; Step A2, after mixing deionized water, dodecylbenzene sulfonic acid and emulsifier, heat to 40-50°C and stir for 30 minutes, then slowly add the mixture of ethyl orthosilicate and KH-570, stir and react for 1.5-2.5 hours, cool to room temperature, adjust the pH to 8-9, heat to 75-85°C, add potassium persulfate, then add the acrylate mixture dropwise, add an equal amount of potassium persulfate and react for 2-3 hours, demulsify, filter, wash and dry to obtain a modified toughening agent.

2. A high temperature resistant cable material according to claim 1, characterized in that: In step A1, the usage ratio of ethylenediaminetetramethylenephosphonic acid, 1,4-dioxane and hydroxyethyl acrylate is 0.01 mol:50 mL:0.02-0.04 mol.

3. A high temperature resistant cable material according to claim 1, characterized in that: In step A2, the dosage ratio of deionized water, dodecylbenzenesulfonic acid, emulsifier, tetraethyl orthosilicate, KH-570, acrylate mixture and potassium persulfate is 30-40 mL: 0.35-0.4 g: 0.05-0.1 g: 23-24 g: 1-2 g: 79.25-87.25 g: 0.6 g.

4. A high temperature resistant cable material according to claim 3, characterized in that: The acrylate mixture is prepared by mixing and stirring acrylic acid, butyl acrylate, methyl methacrylate, phosphate derivatives, sodium dodecyl sulfate and deionized water in a mass ratio of 1-3:10-15:3-4:10-15:0.25:

50.

5. A high temperature resistant cable material according to claim 1, characterized in that: The composite stabilizer is a mixture of zinc stearate and an organic stabilizer, wherein the mass ratio of zinc stearate to the organic stabilizer is 1-3:1-3.

6. A high temperature resistant cable material according to claim 5, characterized in that: The organic stabilizer is prepared by the following steps: Step B1, dispersing 1-(3-aminopropyl)imidazole and sodium hydroxide in acetonitrile, recorded as solution 1; dispersing cyanuric chloride and acetonitrile evenly in an ice water bath, slowly adding solution 1 dropwise, and reacting at 0-5° C. for 2-4 hours to obtain an intermediate product; Step B2, 5-aminoisophthalic acid and sodium hydroxide are dispersed in acetonitrile, recorded as solution 2; the intermediate product is heated to room temperature, and 1 / 2 of solution 2 is slowly added dropwise, the temperature is raised to 45-55°C for reaction for 4-6h, and then the temperature is raised to 90°C, and the remaining solution 2 is slowly added dropwise, and the temperature is maintained at reflux for reaction for 5-7h, and the pH of the system is adjusted to 6.5-7, and the solvent is distilled off to obtain an organic stabilizer.

7. A high temperature resistant cable material according to claim 6, characterized in that: In step B1, the usage ratio of cyanuric chloride, acetonitrile and solution 1 is 0.01-0.03 mol: 100 mL: 50 mL, and the usage ratio of 1-(3-aminopropyl)imidazole, sodium hydroxide and acetonitrile in solution 1 is 0.01-0.03 mol: 0.04-0.12 g: 50 mL.

8. A high temperature resistant cable material according to claim 6, characterized in that: The usage ratio of 5-aminoisophthalic acid, sodium hydroxide and acetonitrile in solution 2 of step B2 is 0.02-0.06 mol: 0.08-0.24 g: 100 mL.

9. A method for preparing the high temperature resistant cable material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight: mixing PVC resin, modified toughening agent, composite stabilizer, nano-silicon dioxide, lubricant and antioxidant at 100-120° C. for 5-10 minutes, then heating to 150-170° C., adding plasticizer and maleic anhydride grafted EPDM rubber and continuing to stir for 4-7 minutes to obtain a mixture; Step S2: placing the mixed material in a twin-screw extruder for extrusion and granulation to obtain a high temperature resistant cable material.

10. The method for preparing a high temperature resistant cable material according to claim 9, characterized in that: In step S2, the screw speed of the twin-screw extruder is 400-600 rpm / min, and the die discharge temperature is 175-185°C.

Citation Information

Cited By

  • Flame-retardant polyvinyl chloride plastic particles and preparation method thereof

    CN121006007A